2003
DOI: 10.1007/s10143-003-0267-8
|View full text |Cite
|
Sign up to set email alerts
|

Genes and pathways driving glioblastomas in humans and murine disease models

Abstract: Human malignant gliomas arise from neural progenitor cells and/or dedifferentiated astrocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 98 publications
(116 reference statements)
1
42
0
4
Order By: Relevance
“…Because chromosome instability is associated with tumor progression, these findings indicate that loss of BCCIP may be associated with tumor aggression. The human BCCIP gene is located at 10q26 (Liu et al, 2001), which has been implicated in many forms of human tumors, including astrocytic brain tumors (Rasheed et al, 1992;Maier et al, 1998;Merlo, 2003;Ohgaki et al, 2004). We have previously shown that BCCIP expression is downregulated in kidney cancer (Meng et al, 2003), BCCIPa expression was not detectable in astrocytic brain cancer cell line A172 (Liu et al, 2001), and BCCIP deletion has been suggested in a brain tumor cell line (Roversi et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Because chromosome instability is associated with tumor progression, these findings indicate that loss of BCCIP may be associated with tumor aggression. The human BCCIP gene is located at 10q26 (Liu et al, 2001), which has been implicated in many forms of human tumors, including astrocytic brain tumors (Rasheed et al, 1992;Maier et al, 1998;Merlo, 2003;Ohgaki et al, 2004). We have previously shown that BCCIP expression is downregulated in kidney cancer (Meng et al, 2003), BCCIPa expression was not detectable in astrocytic brain cancer cell line A172 (Liu et al, 2001), and BCCIP deletion has been suggested in a brain tumor cell line (Roversi et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Survivin has emerged as an attractive therapeutic target and potentially important prognostic marker in many tumor types, including human gliomas (Ambrosini et al, 1997;Adida et al, 1998Adida et al, , 2000Kawasaki et al, 1998;Lu et al, 1998;Monzo et al, 1999;Asanuma et al, 2000;Islam et al, 2000;Olie et al, 2000;Tanaka et al, 2000;Grossman et al, 2001;Smith et al, 2001;Merlo, 2003). There have been four recent studies demonstrating that Survivin expression is associated with glioma progression from low-to high grade (Tan et al, 1993;Chakravarti et al, 2002;Sasaki et al, 2002;Kajiwara et al, 2003;Katoh et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…GBM has a complex tumor structure consisting of accumulating tumors cells, abnormal vessel and necrotic debris. The increasing tumor mass leads to increased capillary and venous collapse (Merlo, 2003). The new formed vessels are structurally and functionally abnormal, and leaky, leading to edema, and low oxygen tension (Bani-Yaghoub et al, 2006).…”
Section: Midkine and Glioblastomamentioning
confidence: 99%